Bahasa Inggris - Ni Komang Dwi Eka Yuliati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Getting data on the mother language for primary students can be challenging in a multilingual setting as Indonesia. There are around 700 spoken languages ​​spoken in Indonesia. It is often challenging to assess a young learner first language directly because of the shortfall of assets accessible in each language. Getting information on every child's mother tongue acquisition is very important for bridging teaching instruction in primary years, as does in reading. This study's objective was to assess the validity and reliability of an adapted parent questionnaire on the first language development of Indonesian learners that is not specific to a particular language or cultural group. This research and development use a 4-D model (define, design, development, disseminate). The defined stage consists of focus group discussion resulting in the need for mother-tongue information to support instruction in reading comprehension. The design stage is the adaptation of the Alberta Language and Development Questionnaire (ALDeQ)'s existing questionnaire leading to the parent information questionnaire design fitted into the Indonesian context. Field tests and data analysis are conducted in the developmental stage. This descriptive quantitative research did not go through the dissemination stage because not being developed wider. The Gregory content validation formula obtained a score of 1, which was categorized as very high, indicating that the instrument is eligible. The Product Moment empirical validity indicates a high validity. Reliability tests using Cronbach's Alpha formula showed a value of 0.86 which means very high.